Analisis Kepuasan Kerja Pegawai di MTsN 40 Jakarta Barat Menggunakan Pendekatan Importance-Performance Analysis (IPA) - Kayla Aura Rahma; Nanang Alamsyah; Wendy Febrianty Mardhiyah; Hafiza Aprilia (Yayasan Literasi Sains Indonesia, 2026)
Employee job satisfaction is an important factor that influences organizational effectiveness and the quality of work outcomes. This investigation aims to measure the level of job satisfaction among employees at MTsN 40 Jakarta Barat and identify priority attributes for improvement according to the Importance Performance Analysis (IPA) method. Data were collected from 30 respondents utilizing a structured questionnaire consisting of ten job satisfaction indicators. The results show that several attributes exhibit negative gaps, indicating that the performance perceived by employees has not fully met their expectations. The IPA mapping reveals that Productivity and Leadership Qualities fall into Quadrant I (Concentrate Here), representing the most critical areas requiring immediate improvement. Meanwhile, Knowledge of Job, Adaptability, and Interpersonal Relations are placed in Quadrant II (Keep Up the Good Work), reflecting strong performance in aspects considered important. Quality of Work, Dependability, Judgment, and Initiative and Resourcefulness are categorized into Quadrant III (Low Priority), while Performance is located in Quadrant IV (Possible Overkill). Overall, the main sources of dissatisfaction stem from limited support for work processes and suboptimal leadership, rather than inadequate technical abilities. Therefore, strengthening leadership effectiveness, improving workflow efficiency, and enhancing internal communication are recommended to increase employee satisfaction sustainably.